WORKSHOP DAN PENDAMPINGAN GURU DALAM MENDESAIAN BAHAN AJAR DIGITAL DI SMK MUHAMMADIYAH PONJONG - Andriyani, Andriyani; Firmansyah, Furqon; Cholid, Fahmi; Setyawan, Novid Dony; Asyari, Diana (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
This Prodamat activity aims to provide workshops and assistance to teachers in designing digital teaching materials at Ponjong Muhammadiyah Vocational School. Prodamat's activity methods include: measuring teachers' abilities in designing digital teaching materials, workshops introducing Flip PDF Corporate Edition software, assisting in designing digital teaching materials with Flip PDF Corporate Edition software, and evaluating the effectiveness of workshops and mentoring activities on teachers' ability to design the teaching materials. The results of the activity feedback show the effectiveness of the implementation of the activity because the average participant assessment is at a high and highest level, namely a score of 4 and a score of 5. This shows a very good response to aspects of the usefulness of the event, tight time with the event structure, completeness of the material, attitude committee, suitability of the presenter to the event theme, clarity of the event, mastery of the material, interaction with participants, and management/time management